BRS Celeste - new soybean cultivar to the grain production system of the Brazilian savannah - Souza, Plínio Itamar de Mello de; Spehar, Carlos Roberto; Moreira, Claudete Teixeira; Kiihl, Romeu Afonso de Souza; Almeida, Leones Alves de; Neto, Austeclínio Lopes de Farias; Amabile, Renato Fernando; Assunção, Mauricio Silva; Faria, Luis Claudio de; Filho, Gottfried Urben; Monteiro, Pedro Manoel Figueira de Oliveira (Pesquisa Agropecuaria Brasileira, 2000)
Maintenance or improvement of technology to soybean cultivation is necessary to reach economical productivity in the Brazilian Savannah, where it has shown to be superior to that obtained in the South of Brazil. New cultivars are among the contributions of research to high crop performance and yield stability. The soybean cv. BRS Celeste is an alternative to suit growers demand. It belongs to the same maturity group of cv. BR/EMGOPA 314 (Garça Branca), although it has higher yielding and shows resistance to the main diseases, especially stem canker (Diaporthe phaseolorum f. sp. meridionalis).